Association of self-reported anxiety and depressive symptoms with incident hypertension among young adults - Ko-Huan Lin; Chu-Yu Hsu; Yi-Chiung Hsu; Kun-Zhe Tsai; Yun-Chen Chang; Wei-Chun Huang; Xuemei Sui; Carl J. Lavie; Gen-Min Lin (Frontiers in Cardiovascular Medicine, 2026)
Aims Previous studies have revealed inconsistent results regarding the association between depressive symptoms and hypertension. Other mood disorders, such as anxiety, usually coexist with depression and require exploration of their impact on depression in patients with hypertension. Methods and results This study included 2,448 Taiwanese military personnel who were free of hypertension at baseline. Mood status was assessed using the Brief Symptoms Rating Scale-5 (BSRS-5) score, which includes five domains of depressive symptoms, anxiety, interpersonal sensitivity, insomnia, and hostility, which were evaluated separately using a five-point Likert-type scale of 0–4. Incident hypertension was defined according to the latest American guidelines, and follow-up was conducted from 2014 until the end of 2020. Multivariable Cox regression analysis was used to determine the associations of each mood item and a combination of the significant items with incident hypertension, with adjustments for potential confounders. Results There were 125 new-onset stage 2 hypertension cases (5.2%) during a median follow-up period of 6.0 years. The sum of the BSRS-5 scores was not linked to new-onset stage 2 hypertension [hazard ratio (HR) and 95% confidence interval (CI): 1.05 (0.99–1.11)]. Among the five mood domains, depressive symptoms (score ≥1) were significantly associated with new-onset stage 2 hypertension [HR 1.68 (95% CI 1.16–2.45)], whereas anxiety symptoms (score ≥1) showed a borderline association [HR 1.43 (95% CI 0.99–2.08)]. Neither of the associations was linear. The presence of depressive symptoms alone or anxiety symptoms alone (one score ≥1 and another score = 0) was not associated with stage 2 hypertension (HR: 1.11, p = 0.71), whereas both scores ≥1 were associated with a higher risk of stage 2 hypertension [HR: 1.71 (95% CI 1.14–2.57)]. Conclusions Our findings suggest that the coexistence of self-reported anxiety and depressive symptoms may increase the risk of stage 2 hypertension in young military adults.